ANALISIS ABSOLUTE DAN OBLIQUE DALAM BAHASA KERINCI ISOLEK PULAU TENGAH - Nova Rina; Fadlul Rahman (Masyarakat Linguistik Indonesia Universitas Andalas, 2016)
This research study in phonological field, aims of this research to discribe rhyme alternation on form of absolute and oblique in Kerinci language isolect pulau tengah. The purpose of this research are 1) to documenting Kerinci language isolect Pulau Tengah that threatened by Indonesian standart, Jakarta Indonesia, Minangkabau language, and most seriously threathened by Kerinci koine 2) the result of this research about description of Kerinci language isolect Pulau Tengah will be useful for other Malayic language researcher especially in remote areas of Sumatera and 3) give langauge contribution significantly for Kerinci society especially for Pulau Tengah society. This research found 19 rhyme alternation in G-words, 20 rhyme alternation in K-words, 16 vocal sequences, 28 consonant clusters, 12 consonant sequences, and base on silable phonotactic rules in Kerinci language isolect Pulau Tengah, it found six rules; V, VC, CV, CVC, CCV, and CCVC.